Utility of Ischemia Modified Albumin as an Early Marker for Diagnosis of Acute Coronary Syndrome - Mishra, Bijaya; Pandey, Sunil; Niraula, Surya Raj; Rai, Bijendra Kumar; Karki, Prahlad; Baral, Nirmal; Lamsal, Madhab (Journal of Nepal Health Research Council, 2018)
Background: The diagnosis of acute coronary syndrome remains challenging, as cardiac troponins and creatine kinase-MB do not detect myocardial ischemia. Ischemia modified albumin is biomarker positive within 6-10 minutes following ischemic onset, where oxygen free radicals leads to reduction in binding capacity of human serum albumin to transitional metal-cobalt. The objective of this study was to compare ischemia modified albumin between acute coronary syndrome patients and healthy controls, and evaluate diagnostic performance of ischemia modified albumin compared to cardiac troponins, creatine kinase-MB and electrocardiogram in acute coronary syndrome patients.Methods: Fifty ACS patients and 50 healthy controls were enrolled in this cross-sectional study. Ischemia modified albumin was measured after addition of known amount of cobalt to human serum albumin, followed by spectrophotometric determination of unbound cobalt fraction at 470 nm using dithiothreitol as coloring agent. Independent student t-test and One-way ANOVA to compare differences of mean between groups; diagnostic sensitivity and specificity of ischemia modified albumin was determined by receiver operating characteristic curve; McNemar-test was used to assess diagnostic performance of entire test parameters, when used alone and in combinations.Results: Ischemia modified albumin was significantly higher in acute coronary syndrome patients compared to controls (0.823±0.191 vs 0.410±0.081)(p